1996
DOI: 10.1055/s-2006-957867
|View full text |Cite
|
Sign up to set email alerts
|

Non-Phenolic Linear Diarylheptanoids fromCurcuma xanthorrhiza: A Novel Type of Topical Anti-Inflammatory Agents: Structure-Activity Relationship

Abstract: The topical anti-inflammatory activity of three non-phenolic linear 1,7-diarylheptanoids, previously isolated from a Thai medicinal plant, Curcuma xanthorrhiza (Zingiberaceae) and four new semi-synthetic derivatives of the naturally occurring compounds were assessed in the murine model of ethyl phenylpropiolate-induced ear edema. The naturally occurring compound 1E,3E,1,7-diphenylheptadien-5-one (6) exerted the most potent anti-inflammatory activity, with an ID50 value of similar magnitude to that of the refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Previous reports have identified the presence of 3 diarylheptanoids from the hexane extract of C. comosa: 1,7-diphenyl-5-hydroxy-(1E)-1-heptane, 5-hydroxy-7-(4-hydroxyphenyl)-1-phenyl-(1E)-1-heptane, and 7-(3,4-dihydroxyphenyl)-5-hydroxy-1-phenyl-(1E)-1-heptane (Suksamrarn et al, 1997). The anti-inflammatory effect of these 3 compounds in C. xanthorrhiza (Jurgens et al, 1994;Suksamrarn et al, 1994) has also been demonstrated in animal models (Claeson et al, 1993(Claeson et al, , 1996.…”
Section: Discussionmentioning
confidence: 95%
“…Previous reports have identified the presence of 3 diarylheptanoids from the hexane extract of C. comosa: 1,7-diphenyl-5-hydroxy-(1E)-1-heptane, 5-hydroxy-7-(4-hydroxyphenyl)-1-phenyl-(1E)-1-heptane, and 7-(3,4-dihydroxyphenyl)-5-hydroxy-1-phenyl-(1E)-1-heptane (Suksamrarn et al, 1997). The anti-inflammatory effect of these 3 compounds in C. xanthorrhiza (Jurgens et al, 1994;Suksamrarn et al, 1994) has also been demonstrated in animal models (Claeson et al, 1993(Claeson et al, , 1996.…”
Section: Discussionmentioning
confidence: 95%
“…In the literature we can find some authors that associate the anti-inflammatory activity of curcumin and its derivatives to the presence of hydroxyl and phenol groups in the molecule, being essential for the inhibition of prostaglandins (PG synthetase) and leucotrienes (LT) (Kiuchi et al 1982, Iwakami et al 1986). On the other hand, some authors suggested that the anti-inflammatory action is associated to the existence of the β-dicarbonylic system, which has the conjugated double bonds (dienes), being responsible for this activity (Claeson et al 1993(Claeson et al , 1996. This system seems to be responsible not only for anti-inflammatory power, but also to antiparasitic activity (Araújo et al 1998(Araújo et al , 1999.…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
“…), which is a medicinal agent in Indonesia. Xanthorrhizol is the main active component of Xan, and has a variety of pharmacological activities, such as anti-metastasis (Choi et al, 2005) and inhibitory effects on nephrotoxicity , as well as anti-cancer and anti-inflammatory effects (Itokawa et al, 1985;Claeson et al, 1993;Claeson et al, 1996). The bactericidal activity of Xan against several oral pathogens has also been reported using planktonic and simple biofilm models Hwang, 2006a, 2006b).…”
Section: Antibacterial Effects Biofilms Curcuma Xanthorrhiza Strepmentioning
confidence: 99%